2019
DOI: 10.1021/jacs.9b06366
|View full text |Cite
|
Sign up to set email alerts
|

Ligand Controlled Ir-Catalyzed Regiodivergent Oxyamination of Unactivated Alkenes

Abstract: An intramolecular Ir(III)-catalyzed regiodivergent oxyamination of unactivated alkenes provides valuable γ-lactams, γ-lactones and δ-lactams. The regioselectivity is controlled by the electronically tunable cyclopentadienyl Ir(III)-complexes enabling oxyamination via either 5-exo or 6-endo pathways. With respect to the mechanism, we propose a highly reactive [3.1.0] bicycle intermediate derived from Ir(V) nitrene-mediated aziridination to be a key intermediate toward the synthesis of γlactams.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
40
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(40 citation statements)
references
References 71 publications
0
40
0
Order By: Relevance
“…For example, Wang reported the copper(II)‐catalyzed 1,2‐oxyamination of alkenes in the amino lactonization of alkenyl carboxylic acids with O ‐benzoylhydroxylamines [3] . Rovis reported the iridium(III)‐catalyzed 1,2‐oxyamination of alkenes in the regiodivergent oxy lactamization of alkenyl carboxamides with carboxylic acids [4] . Besides, the oxyamination of alkenes with amino alcohols or amino acids can furnish heterocycles containing both oxygen and nitrogen, which are basic skeletons of bioactive substances [5] .…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…For example, Wang reported the copper(II)‐catalyzed 1,2‐oxyamination of alkenes in the amino lactonization of alkenyl carboxylic acids with O ‐benzoylhydroxylamines [3] . Rovis reported the iridium(III)‐catalyzed 1,2‐oxyamination of alkenes in the regiodivergent oxy lactamization of alkenyl carboxamides with carboxylic acids [4] . Besides, the oxyamination of alkenes with amino alcohols or amino acids can furnish heterocycles containing both oxygen and nitrogen, which are basic skeletons of bioactive substances [5] .…”
Section: Figurementioning
confidence: 99%
“…[3] Rovis reported the iridium(III)-catalyzed 1,2-oxyamination of alkenes in the regiodivergent oxy lactamization of alkenyl carboxamides with carboxylic acids. [4] Besides, the oxyamination of alkenes with amino alcohols or amino acids can furnish heterocycles containing both oxygen and nitrogen, which are basic skeletons of bioactive substances. [5] As an example using the amino alcohols, Lloyd-Jones and Booker-Milburn reported the palladium(II)-catalyzed 1,1-oxyamination of alkenes with Nprotected amino alcohols ( Figure 1a).…”
mentioning
confidence: 99%
“…Vicinal N,O‐motifs are important skeletons in bioactive molecules, thus inspiring great achievements for their concise constructions such as the Sharpless asymmetric amino‐hydroxylation reaction. In 2019, Rovis developed an oxyamination of olefins using manipulated Cp* ligand on iridium to afford γ ‐ and δ ‐lactams, and γ ‐lactones, via 5‐ exo and 6‐ endo pathways (Scheme ) . Experimental observations indicated that strained azabicyclo[3.1.0] derivatives serve as key intermediates, which might be generated via Ir(V)‐nitrene participating aziridination with an irreversible interception by amines or carboxylic acids nucleophiles.…”
Section: C−n Bond Formationsmentioning
confidence: 99%
“…Mechanistic studies indicated that, with the use of electron‐rich Cp*‐type ligand on Ir(III) catalyst, an Ir(V)‐nitrene involved 5‐ exo type reaction took place to give γ‐lactams. With basic solvent, a 6‐ endo type nucleophilic attack on C−C double bonds proceeded smoothly, followed by an Ir(V)‐nitrene formation to give δ ‐lactams (Scheme ).…”
Section: C−n Bond Formationsmentioning
confidence: 99%
“… 32 36 A rare and recent intramolecular regiodivergent example is the ligand controlled Ir-catalyzed oxyamination process developed by the Rovis group ( Scheme 1 b). 37 , 38 …”
mentioning
confidence: 99%